Antecedents to Thai Automotive Manufacturing Competitive Advantage: A Structural Equation Model Analysis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research was undertaken to develop a structural equation model (SEM) of how technological capabilities (TC),knowledge management (KM), quality management (QM), and the supply chain (SC) affected the competitive advantage (CA)of Thailand’s automotive and auto-parts manufacturing businesses. The research instrument was a questionnaire from whichdata were collected from 515 automotive industry entrepreneurs and managers in Thailand. Subsequently, a confirmatoryfactor analysis (CFA) was done using LISREL 9.1 to determine the model’s fit, followed by an SEM of the variables. Theresults revealed that all causal variables in the model had a positive influence on CAwhich could jointly be explained by thevariance of factors influencing CA (R2) at 78%. The factors affecting CA (ranked from highest to lowest) were QM, the SC,KM, and TC, with total effect(TE) values of 0.72, 0.68, 0.45, and 0.44, respectively. Therefore, to maintain Thailand’sautomotive leadership within ASEAN and maintain a CA on a global scale, this study’s entrepreneurs and managers felt thekey factor was their firm’s ability at QM. Specifically, QM should be focused on the quality management process and strategicplanning, as well as continual improvement and the focus on quality. These factors were closely followed by the SC and eachfirm’s ability to provide good customer service, having a supply chain emergency plan and crisis management system, andfinally, an ongoing supply chain development process. The research also suggests that strategic partnerships with larger,international SC vendors enable a more secure CA. Government policymakers also need to structure their support in a way thataddresses the needs of each type of firm’s TC. Moreover, research & development incubators need to be established, especiallyin light of the Thai government's direction into EVs and the stated goal of 30% EV production by 2030. Universities andvocational education institutions must also be given the means to prepare their next generat ion of knowledge workers for thesenew technologies. Policy and direction also need to be focused, clear, and funded as well, if Thailand wants to retain its currentleadership grasp within the ASEAN automotive manufacturing and auto-parts community.